Scientific Challenges in the Risk Assessment of Food Contact Materials - Muncke, Jane; Backhaus, Thomas; Geueke, Birgit; Maffini, Maricel V; Martin, Olwenn Viviane; Myers, John Peterson; Soto, Ana M; Trasande, Leonardo; Trier, Xenia; Scheringer, Martin (Environmental health perspectives, 2017)
BACKGROUND: Food contact articles (FCAs) are manufactured from food contact materials (FCMs) that include plastics, paper, metal, glass, and printing inks. Chemicals can migrate from FCAs into food during storage, processing, and transportation. Food contact materials' safety is evaluated using chemical risk assessment (RA). Several challenges to the RA of FCAs exist. OBJECTIVES: We review regulatory requirements for RA of FCMs in the United States and Europe, identify gaps in RA, and highlight opportunities for improving the protection of public health. We intend to initiate a discussion in the wider scientific community to enhance the safety of food contact articles. DISCUSSION: Based on our evaluation of the evidence, we conclude that current regulations are insufficient for addressing chemical exposures from FCAs. RA currently focuses on monomers and additives used in the manufacture of products, but it does not cover all substances formed in the production processes. Several factors hamper effective RA for many FCMs, including a lack of information on chemical identity, inadequate assessment of hazardous properties, and missing exposure data. Companies make decisions about the safety of some food contact chemicals (FCCs) without review by public authorities. Some chemical migration limits cannot be enforced because analytical standards are unavailable. CONCLUSION: We think that exposures to hazardous substances migrating from FCAs require more attention. We recommend a) limiting the number and types of chemicals authorized for manufacture and b) developing novel approaches for assessing the safety of chemicals in FCAs, including unidentified chemicals that form during or after production. https://doi.org/10.1289/EHP644.
Keywords: Spojené státy americké; Humans; nebezpečné látky; Hazardous Substances; Plastics; plastické hmoty; obaly potravin; Public Health; veřejné zdravotnictví; lidé; Europe; Food Packaging; United States; kontaminace potravin; Food Contamination; Food Safety; bezpečnost potravin; Risk Assessment; hodnocení rizik; Evropa